Principles of effective communication with patients who have intellectual disability among primary care physicians. Issue 7 (July 2017) - Werner, S.; Yalon-Chamovitz, S.; Tenne Rinde, M.; Heymann, A.D.
Highlights: Familiarity with intellectual disability increased utilization of effective communication principles. Some physicians perceived patients with intellectual disability as unable to make their own healthcare decisions. Attitude of physicians is a main predictor of their communication patterns with patients. Abstract: Objective: Examine physicians' implementation of effective communication principles with patients with intellectual disabilities (ID) and its predictors. Methods: Focus groups helped construct a quantitative questionnaire. The questionnaire (completed by 440 physicians) examined utilization of effective communication principles, attitudes toward individuals with ID, subjective knowledge and number of patients with ID. Results: Subjective knowledge of ID and more patients with ID increased utilization of effective communication principles. Provision of knowledge that allows patients to make their own medical decisions was predicted by more patients with ID, lower attitudes that treatment of this population group is not desirable, less negative affect and greater perception that treatment of this group is part of the physician's role. Effective preparation of patients with ID for treatment was predicted by higher perception of treatment of this group as part of the physician's role, lower perception of this field as undesirable and higher perception of these individuals as unable to make their own choice. Simplification of information was predicted by a greater perception of treatment of this group as part of the physician's role and more negative affect. Conclusion: Greater familiarity may enhance care for these patients. Practice implications: Increase exposure to patients with ID within training.